Digitalization Transformation of Baznas Financial Reports Based On SIMBA 4.0 - Silvany Yanuar, Alya; Makhtum, Ahmad (Universitas Islam Negeri Alauddin Makassar, 2023)
Digital transformation has changed the way businesses and organizations operate in the industrial 4.0 era. One of the areas affected is the organization's financial statements. The National Amil Zakat Agency (BAZNAS) is an organization engaged in the socio-religious field that collects and manages zakat, infaq, and alms funds. BAZNAS financial reports are important to show accountability and transparency in the management of zakat funds. Therefore, the transformation of digitalization of BAZNAS financial reports is important in this digital era. This study aims to analyze the implementation of the Management Information System for the National Amil Zakat Agency (SIMBA BAZNAS) in Sidoarjo Regency as a tool for digitizing BAZNAS financial reports. This study uses a qualitative approach by conducting interviews with SIMBA BAZNAS managers and analysis of related documents. The results of the study show that SIMBA BAZNAS has succeeded in helping BAZNAS Sidoarjo Regency in the transformation of digitizing financial reports. In its implementation, SIMBA BAZNAS provides various features and capabilities, such as automatic report generation, digital transaction recording, and more effective financial management arrangements. In addition, SIMBA BAZNAS also helps improve accuracy and speed in preparing financial reports. However, there are also several obstacles in the implementation of SIMBA BAZNAS, such as the lack of outreach and training to users, so that some users do not understand how to use SIMBA BAZNAS optimally. Therefore, it is hoped that there will be efforts to increase outreach and training in using SIMBA BAZNAS so that it can be used more optimally in digitizing BAZNAS financial reports in the future.